VIDEO SIGNAL RECORDING AND REPRODUCING DEVICE - AWAMOTO SHIGERU; MATSUDA TOYOHIKO; NISHINO SHOICHI (1994)
PURPOSE:To ameliorate the visual picture quality of a part to which data error is corrected with respect to the video signal recording and reproducing device applying high efficient coding to a video signal and recording and reproducing the processed signal. CONSTITUTION:The device is provided with an inter-frame arithmetic operation circuit 2, a recording and reproducing device 7, an error correction circuit 9, an inter-frame inverse arithmetic operation circuit 13, and after data obtained by addition and subtraction of data between two consecutive frames at the inter-frame arithmetic operation circuit 2 are subject to high efficiency coding, the result is recorded/reproduced by the recording and reproducing device 7, high efficiency coding is applied at reproduction and an inter-frame inverse arithmetic operation circuit 13 applies addition subtraction processing to the data to obtain a reproduced video signal. An inter-frame inverse arithmetic operation circuit 13 outputs only subtraction processing data to a port to which error correction is implemented by the error correction circuit 9.